Point-kernel method for radiation fields simulation - Prokhorets, M.I.; Prokhorets, S.I.; Khazhmuradov, M.A.; Rudychev, E.V.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2007)
Point-kernel source method for radiation field calculation using Mercure-3 code is considered. Calculation results are shown to be in perfect agreement with those obtained using MCNP code.